Toll‐like receptors as novel therapeutic targets for herpes simplex virus infection. (2nd July 2019) - Jahanban‐Esfahlan, Rana; Seidi, Khaled; Majidinia, Maryam; Karimian, Ansar; Yousefi, Bahman; Nabavi, Seyed Mohammad; Astani, Akram; Berindan‐Neagoe, Ioana; Gulei, Diana; Fallarino, Francesca; Gargaro, Marco; Manni, Giorgia; et al.
Summary: Seropositivity for HSV reaches more than 70% within the world population, and yet no approved vaccine exists. While HSV1 is responsible for keratitis, encephalitis, and labialis, HSV2 carriers have a high susceptibility to other STD infections, such as HIV. Induction of antiviral innate immune responses upon infection depends on a family of pattern recognition receptors called Toll‐like receptors (TLR). TLRs bridge innate and adaptive immunity by sensing virus infection and activating antiviral immune responses. HSV adopts smart tricks to evade innate immunity and can also manipulate TLR signaling to evade the immune system or even confer destructive effects in favor of virus replication. Here, we review mechanisms by which HSV can trick TLR signaling to impair innate immunity. Then, we analyze the role of HSV‐mediated molecular cues, in particular, NF‐κB signaling, in promoting protective versus destructive effects of TLRs. Finally, TLR‐based therapeutic opportunities with the goal of preventing or treating HSV infection will be discussed.